Trace element composition of marine surface sediments of the Canadian Arctic - Brice, Camille; Montero-Serrano, Jean-Carlos; St-Louis, Richard; Rosabal, Maikel (PANGAEA, 2025)
Concentrations of labile trace metals, including rare earth elements (REEs), were measured in the <150 μm fraction of 141 terrestrial and marine surface sediment samples in the Canadian Arctic. This study evaluates the current state of metal contamination in the region using a geochemical survey coupled with pollution indices and sediment quality guidelines. Samples were collected during the ArcticNet 2016-2022 expeditions onboard the Canadian Coast Guard icebreaker Amundsen in the Canadian Arctic. The marine sediments were sampled with a box corer and the surface uppermost 1 cm of each box core was sampled. Geochemical data were measured with partial acid digestion and mass spectrometry.
Keywords: Canadian Arctic; Marine surface sediments; partial digestion; Pollution indices; Rare earth elements; sediment quality; trace metals